Morphological and Physiological Adaptations of Venus Slipper (Paphiopedilum) - Durotun Ainiyah; Nur Kholiq; Isfina Nurfaidatur Rohmah; Su’udi, Mukhamad (Konservasi Hayati, 2024)
Paphiopedilum, commonly known as venus slipper or lady slipper, is a genus of orchids that boasts over 70 species, most of which are critically endangered to endangered. These orchids are characterized by the presence of a sac on the flower that serves a unique function closely related to pollination. The pollination of Paphiopedilum is facilitated by bees, which are lured to the flower by producing pheromones such as €-β-farnese and β-pinene. Pouched orchids also produce compounds from the terpenoid group to synthesize a scent that attracts pollinators. Paphiopedilum orchids have evolved a fascinating mechanism to ensure successful pollination. They trap pollinators by making the pollination area slippery so that when the pollinator enters the area, it is likely to slip and try to get out along with the attached pollen. This unique mechanism ensures that the pollen is transferred effectively, increasing the chances of successful fertilization.